Suitability of Drinking Water Sources from Nyaruzinga Wetland for Domestic Use in Bushenyi Municipality, Uganda - Muhangane, Lauben; Nkurunungi, John B.; Yatuha, Jane; Andama, Morgan (Journal of Water Resource and Protection, 2017)
This study determined the physico-chemical and bacterial quality of raw (borehole,springs, wells) and tap water sources from Nyaruzinga wetland for domestic use in Bushenyi Municipality. Forty samples of raw water were randomly collected from Kacuncu, Kyeitembe and Kikuba tributaries of the wetland and 40 samples of tap water generated from the same wetland were randomly drawn from Ishaka, Nyakabirizi and Central divisions of the Municipality. The samples were analyzed for apparent colour (AC), turbidity, electrical conductivity (EC), total hardness, pH, total iron, residual alum, free residual chlorine and faecal coliforms using standard methods and their values compared with standard local UNBS (2008) and international WHO (2011) drinking water quality guidelines. The results showed that the mean pH of the protected spring below Kikuba Hill (5.21); the AC (Pt/Co) of the borehole below Bweranyangi Junior School (17.28) and the surface well below Nyandozo Primary School (157.58) both situated in Kacuncu as well as the free residual chlorine (mg/L) in tap water at Kanyamabona Trading Centre, Ishaka division (0.192) were below the standard values of WHO (pH, 6.0 - 8.0; free residual chlorine, 0.2 - 0.5) and UNBS (AC, <15). The electrical conductivity
Keywords: Bacterial Load; Bushenyi Municipality; Drinking Water Sources; Physico-Chemical Parameters